COMPARING SUBJECTS EWGSOP SARCOPENIC STATUS AND THEIR CLINICAL FRAILTY SCALE LEVEL - Juby, A.; Davis, C.; Minimaana, S. (Innovation in aging, 2017)
The European Working Group of Sarcopenia in Older People (EWGSOP) classifies normal, presarcopenia, sarcopenia, and severe sarcopenia depending on lean muscle mass, grip strength and gait speed. The Clinical Frailty Scale (CFS) has 9 classifications. Prevalence of sarcopenia and frailty increase with age. Are they two sides of the same coin? Seniors participating in an exercise study were evaluated for sarcopenic status. Blinded to this information, they were evaluated using the CFS and classified accordingly. Data was obtained from 39 participants (6 men), average age 75.7years (67–90). Average MMSE 29.1 (22–30), MoCA 26.4 (18–30). 11 were normal, 11 were obese, the remainder various stages of sarcopenia. 24 were CFS 3 or higher. Poor correlation was found between EWGSOP sarcopenic status and CFS (R=0.43), lean muscle mass (appendicular lean mass/height2) and CFS (R=0.21 in women), EWGSOP grip strength cut-offs and CFS (R=0.46). However, good correlation was found between CFS and 6m absolute walk time (R=0.82) and gait speed (R=-0.61). This study is limited by fewer individuals in the sarcopenic or frail spectrum. This study suggests there is poor correlation between sarcopenic status (as defined by EWGSOP criteria), absolute muscle mass or grip strength and CFS. However, there was good correlation with gait time and speed, suggesting that functional measures of muscle are more important than absolute muscle mass in the development of frailty. Sarcopenia, as defined by EWGSOP does not equate to frailty as defined by CFS. The use of standardized definitions has important implications for research into potential therapeutic interventions.